Energy availability in elite female Australian football players - Condo, D.; Young, C.; Jardine, J.; Kelly, M.; Slater, G.; Carr, A. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
INTRODUCTION: Energy demands of the Australian Football League-Women`s (AFLW) competition, combined with limited investment in nutrition support, may result in issues regarding energy availability (EA). There is little published data on EA in female team-sport athletes, with most research focusing on the risk of low energy availability (LEA), as inferred from subjective questionnaires likely due to the difficulty in quantifying energy expenditure (EE). The aims of this study were to quantify EA in AFLW players while contrasting outcomes against validated questionnaires and to investigate associations between dietary intake, EE and EA in AFLW players.